Toll signal transduction pathway in bivalves: complete cds of intermediate elements and related gene transcription levels in hemocytes of immune stimulated Mytilus galloprovincialis - Toubiana M; ROSANI, UMBERTO; Giambelluca S; Cammarata M; Gerdol M; Pallavicini A; VENIER, PAOLA; Roch P. (Developmental & Comparative Immunology, 2014)
Based on protein domain structure and organization deduced from mRNA contigs, 27 transcripts of the Toll signaling pathway have been identified in the bivalve, Mytilus galloprovincialis. Identical searches performed on publicly available M. edulis ESTs revealed 11 transcripts, whereas searches performed in genomic and new transcriptome sequences of the Pacific oyster, Crassostrea gigas, identified 21 Toll-related transcripts. The remarkable molecular diversity of TRAF and IKK coding sequences of C. gigas, suggests that the sequence data inferred from Mytilus cDNAs may not be exhaustive. Most of the Toll pathway genes were constitutively and ubiquitously expressed in M. galloprovincialis, although at different levels, and clearly induced after in vivo injection with bacteria. Such over transcription was more rapid and intense with Gram-negative than with Gram-positive bacteria. Injection of a fungus modulated the transcription of few Toll pathway genes, with the induction levels of TLR/MyD88 complex being always less intense. Purified LPS and β-glucans had marginal effect whereas peptidoglycans were ineffective. At the moment, we found no evidence of an IMD transcript in bivalves. In conclusion, mussels possess a complete Toll pathway which can be triggered either by Gram-positive or Gram-negative bacteria.